Pengaruh Latihan Small Sided Games Terhadap Ketepatan Passing Sepakbola - Aliansyah; Hakim, Luqmanul; Puriana, Ramadhani Hananto; Darisman, Eka Kurnia (Motion: Journal Research of Physical Education, 2025)
The purpose of this research is to find out whether or not there is an effect of small sided games training on the accuracy of passing in student soccer games at Madrasah Aliyah Nurul Ichsan. This study uses a quantitative research approach. The sampling technique used simple random sampling of MA Nurul Ichsan students with a sample of 20 male students. Using statistical analysis method with paired sample t-test. Based on the results of the paired sample t-test, it can be seen that the p-value in the experimental group is 0.002 and the control group is 0.068. When compared with alpha, the value of the experimental group was smaller (0.002 <0.05) which stated that H0 was rejected and H1 was accepted. This indicates that there is a significant difference between the experimental group and the control group. So it can be concluded that the practice of small sided games affects the accuracy of passing in football games for class X students at Madrasah Aliyah Nurul Ichsan